Preclinical and clinical investigation of intratumoral chemotherapy pharmacokinetics in DIPG using gemcitabine. Issue 1 (24th February 2020) - Green, Adam L; Flannery, Patrick; Hankinson, Todd C; O'Neill, Brent; Amani, Vladimir; DeSisto, John; Knox, Aaron; Chatwin, Hannah; Lemma, Rakeb; Hoffman, Lindsey M; Mulcahy Levy, Jean; Raybin, Jennifer; et al.
Abstract: Background: Hundreds of systemic chemotherapy trials in diffuse intrinsic pontine glioma (DIPG) have not improved survival, potentially due to lack of intratumoral penetration, which has not previously been assessed in humans. Methods: We used gemcitabine as a model agent to assess DIPG intratumoral pharmacokinetics (PK) using mass spectrometry. Results: In a phase 0 clinical trial of i.v. gemcitabine prior to biopsy in children newly diagnosed with DIPG by MRI, mean concentration in 4 biopsy cores in patient 1 (H3K27M diffuse midline glioma) was 7.65 µM. These compare favorably to levels for patient 2 (mean 3.85 µM, found to have an H3K27-wildtype low-grade glioma on histology), and from a similar study in adult glioblastoma (adjusted mean 3.48 µM). In orthotopic patient-derived xenograft (PDX) models of DIPG and H3K27M-wildtype pediatric glioblastoma, gemcitabine levels and clearance were similar in tumor, pons, and cortex and did not depend on H3K27 mutation status or tumor location. Normalized gemcitabine levels were similar in patient 1 and the DIPG PDX. Conclusions: These findings, while limited to one agent, provide preliminary evidence for the hypotheses that lack of intratumoral penetration is not why systemic chemotherapy has failed in DIPG, and orthotopic PDX models can adequately model intratumoral PK in human DIPG.